OKN Asymmetry in Human Subjects: A Literature Review. (8th March 2013) - Knapp, Christopher M.; Proudlock, Frank A.; Gottlob, Irene
Abstract: Optokinetic nystagmus (OKN) is a reflex eye movement induced by motion of the whole or a large proportion of the visual field. It can be horizontal, vertical, and torsional in direction and consists of two basic components, a slow tracking movement and a rapid recovery saccade. Two forms of OKN exist: "look" and "stare" OKN. There is strong evidence that horizontal OKN is symmetrical in normal healthy adults and that the OKN gains can be influenced by a variety of different factors including target size, shape, contrast, and velocity. Vertical OKN on the other hand is less well understood, although there is a belief that vertical OKN is asymmetrical with an upward preference. Recent publications contradict this assertion. In this article a comprehensive literature review was carried out to determine whether a vertical OKN asymmetry exists in healthy subjects and to explain any anomalous findings.